Peran Guru dalam Meningkatkan Kemampuan Siswa untuk Melafalkan Makharijul Huruf di Pondok Tahfidz Hazima Kecamatan 2x11 Kayutanam - Nurfadillah, Nurfadillah; Ikhlas, Al (TSAQOFAH, 2025)
The instruction of makharijul huruf is a fundamental aspect of Qur’anic education, particularly for first-grade students at Pondok Tahfidz Hazima, who are in the early stages of developing accurate reading skills in accordance with tajwid rules. This study aims to identify the role of teachers in enhancing students' ability to pronounce makharijul huruf correctly. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. The findings indicate that teachers play a strategic role in guiding students, notably through the formation of study groups based on skill levels and the consistent application of the talaqqi method. Furthermore, collaboration among teachers, parents, and the institution serves as a key supporting factor in the success of the learning process. Through intensive guidance and regular direct correction, students demonstrated significant improvement in their pronunciation of makharijul huruf over a one-year period. The study concludes that the effectiveness of the teacher's role in makharijul huruf instruction is influenced by appropriate pedagogical approaches, institutional support, and active parental involvement. The implications highlight the need to increase the number of teaching staff, utilize diverse learning media, and strengthen communication between teachers and parents to support optimal learning outcomes.